Pengaruh Kompetensi, Empati, Komitmen Organisasi Terhadap Kinerja Karyawan Studi Pada CV. Karya Alam Abadi (KAA) Sampang Cilacap Jawa Tengah - Afif Solaiman (JURNAL EKOBIS DEWANTARA, 2019)
In general, the HR function is to manage, manage as maximally and effectively as possible the Company, in order to obtain maximum performance results. Human resources are the key to running or not a company. In addition, the Company one with another company has its own standards in assessing a job from employees. General assessment benchmarks are employee discipline, abilities, skills, family background, work experience, social and demographic levels. Thus, an employee in a company must have the knowledge, skills, attitudes, values, or personal characteristics that enable workers to achieve success in completing their work through achieving results or success in completing their tasks so that goals within the company can be achieved and provide satisfaction for consumers. In addition, employees at CV. Cilacap's Eternal Nature Work also needs to have a spirit of patriotism in the community such as helping others who need help. If the above discusses the need for adjustments to the employee's environment, also employees must have a commitment to their company, such as employees performing tasks assigned in accordance with the boundaries of the assignments given, as well as resolving company goals with employees. so that the relationship between the employee and his boss can be harmoniously established.